Paradigm Shift in Investment Property Valuation Theory and Practice: Nigerian Practitioners’ Response. - Babawale, G.K (Mediterranean Journal of Social Sciences, 2012)
This paper examined the response of Nigerian property valuation professionals to observed shifts in valuation theory, valuationconstruction process, firms’ structure and regulatory framework, over time (particularly in the UK from where Nigerian practice took itsroot), with the aim of ascertaining the dynamism of the local practice and the extent to which it is keeping pace with internationalstandards and best practices. Structured questionnaire was used to elicit information from local practitioners. The study revealedcomparatively negligible shifts in valuation theory, valuation construction process and firms’ structure; while the regulatory frameworkhas witnessed remarkable shifts. The study provides a benchmark for gauging the development of real estate valuation in Nigeria in thelight of contemporary international standards and best practices. The results point the way to improving valuation practice in Nigeria, andalso revealed the extent to which such improvements are feasible. The study identified the academia, individual valuation firm, and theNigerian Institution of Estate Surveyors and Valuers (NIESV) as the major drivers of the required shifts in theory and practice. The studyalso proffered the means whereby the required shifts can be fast-tracked including an overhauling of the training syllabus; creation of acentral database; and a stronger collaboration between the academia and the practitioners particularly in research and informationdissemination.